Evaluating The Efficacy And Safety Of Tranexamic Acid To Hydroquinone And Triple Combination Cream In The Treatment Of Melasma - A. A. Ayu Adisti Nina Yuniandari; Diana Wijayanti (Syntax Corporation Indonesia, 2022)
Background: Melasma is acquired skin condition characterized by sporadic hyperpigmented macules or patches that affects photo-exposed areas which occur chronically. Melasma seriously impairs a patient’s quality of life. Current treatments for melasma include hydroquinone, corticosteroids, retinoids, natural substances, and triple combination creams (TCC), which demonstrate variable efficacy and side-effect profiles. Melasma can now be treated with tranexamic acid (TA), a well-known anti-fibrinolytic drug. Oral, topically applied, and procedural techniques were used to administer TA. Purpose: This review evaluating the efficacy and safety of tranexamic acid to hydroquinone and triple combination cream in the treatment of melasma and suggests steps that need to be taken to mainstream TA use in clinical settings. Review: Among the recent melasma treatments are including hydroquinone (HQ), triple combination topicals, and regular use of broad-spectrum sunscreen. .1 Because plasmin has been shown to have melanogenic properties, tranexamic acid (TA) is an essential therapy option for melasma due to its anti-plasmin (and consequently anti-fibrinolytic) properties. Recent research has shown that melasma-affected skin has enhanced vascularity and VEGF expression in the epidermis, suggesting yet another method by which TA may treat melasma clinically. Conclusion: The review revealed that a combination of tranexamic acid and hydroquinone has better efficacy in treating melasma rather than hydroquinone alone. Oral tranexamic acid combined with TCC can prevent recurrence and sustain the outcome.